Torakochirurgia Antithrombotic prophylaxis in cancer patients undergoing thoracic surgery - Fijałkowska, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2007)
Cancer patients undergoing surgery have at least twofold increased risk of postoperative deep vein thrombosis and threefold risk of fatal pulmonary embolism compared to those without cancer. The observed rate of venous thromboembolism (VTE) among cancer thoracic surgery patients not receiving prophylaxis was about 20%, whereas use of prophylaxis significantly reduces the rate of VTE. Based on strong evidence from randomized clinical trials, recent American and Polish guidelines recommend for patients undergoing cancer thoracic surgery higher dose of low molecular weight heparin (LMWH) or 3 times daily unfractionated heparin combined with mechanical prophylaxis. As was shown in two clinical trials, prophylaxis with LMWH continued 2-3 weeks after hospital discharge in cancer surgery reduced the risk of late DVT. Post-hospital discharge prophylaxis with LMWH is suggested.